What do good governments actually do?: An analysis using European procurement data. Issue 3 (10th October 2017) - Popa, Mircea
Abstract : This article looks at what good and bad governments do when performing one of their most central functions, namely public procurement. Some 1.5 million public contracts from across Europe are analyzed through statistical models that compare contracting patterns between good- and poor-governance regions. At the most basic level, the results can be interpreted as a rejection of a conventional view of the relation between governance and institutional choices and outcomes. It is not the case that poorly governed jurisdictions allow more discretion to public officials, that they impose more limits on access to markets, or that they clearly feature more competition, and in fact the opposite often holds. Going beyond this negative finding, the article argues that an alternative view of institutional choice and its connection with governance, in which some discretion and flexibility is desirable, can provide a better explanation of observed patterns, and can have important implications for institutional design.